Expanding the Clinical and Genetic Spectrum of Schmid Metaphyseal Chondrodysplasia: A Seven‐Patient Series Including a Rare Homozygous COL10A1 Case - Ayşe Burcu Doğan Arı; Esra Kılıç (American Journal of Medical Genetics Part A, 2026)
ABSTRACT Schmid metaphyseal chondrodysplasia (SMCD, OMIM #156500) is a skeletal dysplasia characterized by progressive short stature, shortening of the tubular bones, and genu varum. In this study, we present the clinical and genetic findings of patients with COL10A1 variants. A total of seven patients from two unrelated families were included, comprising three children and four adults. The mean age was 6.1 years in children and 41.2 years in adults. Short stature was present in all patients except one, with height SDS ranging from −0.6 to −3.7. All patients exhibited genu varum. Radiographic evaluation revealed coxa vara, metaphyseal irregularities of the long bones, and platyspondyly in all patients; shortening of the tubular bones was observed in six patients, and femoral bowing in two patients. Wormian bones were identified in all six patients from Family 1, representing a previously unreported finding. Two patients underwent hemiepiphysiodesis for the treatment of genu varum. Based on the clinical features, SMCD was suspected in all patients. Genetic diagnosis was established using COL10A1 single‐gene analysis in two index patients, and the identified variants were subsequently confirmed by Sanger sequencing in family members. In Family 1, a heterozygous likely pathogenic variant in COL10A1 , NM_000493.4:c.1744T>G (p.Tyr582Asp), was identified. In Family 2, a homozygous likely pathogenic variant in COL10A1 , NM_000493.4:c.1954C>T (p.Leu652Phe), was detected. Segregation analysis demonstrated heterozygosity for the variant in both clinically unaffected parents. Our findings expand the clinical spectrum of SMCD and underscore the importance of integrating clinical and radiographic evaluation with molecular genetic testing for accurate diagnosis. The identification of a homozygous COL10A1 variant in our patient provides additional support for previous reports demonstrating that SMCD can follow both autosomal dominant and autosomal recessive patterns of inheritance.